Fundamentals of Materials Science and Engineering \ an integrated approach - Callister, William D., Jr., 1940-; Rethwisch, David G. (Hoboken, N.J. : Wiley, 2013)
"Callister and Rethwisch's Fundamentals of Materials Science and Engineering, 4th Edition continues to take the integrated approach to the organization of topics. That is, one specific structure, characteristic, or property type at a time is discussed for all three basic material types -- metals, ceramics, and polymeric materials. This order of presentation allows for the early introduction of non-metals and supports the engineer's role in choosing materials based upon their characteristics. Also discussed are new, cutting-edge materials. Using clear, concise terminology that is familiar to students, Fundamentals presents material at an appropriate level for both student comprehension and instructors who may not have a materials background"--
Machine generated contents note: Chapter 1 - Introduction. 1.1 Historical Perspective 1.2 Materials Science and Engineering 1.3 Why Study Materials Science and Engineering? 1.4 Classification of Materials Materials of Importance-Carbonated Beverage Containers 1.5 Advanced Materials 1.6 Modern Materials Needs 1.7 Processing/Structure/Properties/Performance Correlations Chapter 2 - Atomic Structure and Interatomic Bonding. 2.1 Introduction 2.2 Fundamental Concepts 2.3 Electrons in Atoms 2.4 The Periodic Table 2.5 Bonding Forces and Energies 2.6 Primary Interatomic Bonds 2.7 Secondary Bonding or van der Waals Bonding Materials of Importance-Water (Its Volume Expansion Upon Freezing) 2.8 Molecules Chapter 3 - Structures of Metals and Ceramics 3.1 Introduction 3.2 Fundamental Concepts 3.3 Unit Cells 3.4 Metallic Crystal Structures 3.5 Density Computations-Metals 3.6 Ceramic Crystal Structures 3.7 Density Computations-Ceramics 3.8 Silicate Ceramics 3.9 Carbon Materials of Importance-Carbon Nanotubes 3.10 Polymorphism and Allotropy Material of Importance-Tin (Its Allotropic Transformation) 3.11 Crystal Systems 3.12 Point Coordinates 3.13 Crystallographic Directions 3.14 Crystallographic Planes 3.15 Linear and Planar Densities 3.16 Close-Packed Crystal Structures 3.17 Single Crystals 3.18 Polycrystalline Materials 3.19 Anisotropy 3.20 X-Ray Diffraction: Determination of Crystal Structures 3.21 Noncrystalline Solids Chapter 4 - Polymer Structures 4.1 Introduction 4.2 Hydrocarbon Molecules 4.3 Polymer Molecules 4.4 The Chemistry of Polymer Molecules 4.5 Molecular Weight 4.6 Molecular Shape 4.7 Molecular Structure 4.8 Molecular Configurations 4.9 Thermoplastic and Thermosetting Polymers 4.10 Copolymers 4.11 Polymer Crystallinity 4.12 Polymer Crystals Chapter 5 - Imperfections in Solids 5.1 Introduction 5.2 Point Defects in Metals 5.3 Point Defects in Ceramics 5.4 Impurities in Solids 5.5 Point Defects in Polymers 5.6 Specification of Composition 5.7 Dislocations-Linear Defects 5.8 Interfacial Defects Materials of Importance-Catalysts (and Surface Defects) 5.9 Bulk or Volume Defects 5.10 Atomic Vibrations 5.11 Basic Concepts of Microscopy 5.12 Microscopic Techniques 5.13 Grain Size Determination Chapter 6 - Diffusion 6.1 Introduction 6.2 Diffusion Mechanisms 6.3 Steady-State Diffusion 6.4 Nonsteady-State Diffusion 6.5 Factors That Influence Diffusion 6.6 Diffusion in Semiconducting Materials Material of Importance-Aluminum for Integrated Circuit Interconnects 6.7 Other Diffusion Paths 6.8 Diffusion in Ionic and Polymeric Materials Chapter 7 - Mechanical Properties 7.1 Introduction 7.2 Concepts of Stress and Strain 7.3 Stress-Strain Behavior 7.4 Anelasticity 7.5 Elastic Properties of Materials 7.6 Tensile Properties 7.7 True Stress and Strain 7.8 Elastic Recovery after Plastic Deformation 7.9 Compressive, Shear, and Torsional Deformation 7.10 Flexural Strength 7.11 Elastic Behavior 7.12 Influence of Porosity on the Mechanical Properties of Ceramics 7.13 Stress-Strain Behavior 7.14 Macroscopic Deformation 7.15 Viscoelastic Deformation 7.16 Hardness 7.17 Hardness of Ceramic Materials 7.18 Tear Strength and Hardness of Polymers 7.19 Variability of Material Properties 7.20 Design/Safety Factors Chapter 8 - Deformation and Strengthening Mechanisms 8.1 Introduction 8.2 Historical 8.3 Basic Concepts of Dislocations 8.4 Characteristics of Dislocations 8.5 Slip Systems 8.6 Slip in Single Crystals 8.7 Plastic Deformation of Polycrystalline Metals 8.8 Deformation by Twinning 8.9 Strengthening by Grain Size Reduction 8.10 Solid-Solution Strengthening 8.11 Strain Hardening 8.12 Recovery 8.13 Recrystallization 8.14 Grain Growth 8.15 Crystalline Ceramics 8.16 Noncrystalline Ceramics 8.17 Deformation of Semicrystalline Polymers 8.18 Factors That Influence the Mechanical Properties of Semicrystalline Polymers Materials of Importance-Shrink-Wrap Polymer Films 8.19 Deformation of Elastomers Chapter 9 - Failure 9.1 Introduction 9.2 Fundamentals of Fracture 9.3 Ductile Fracture 9.4 Brittle Fracture 9.5 Principles of Fracture Mechanics 9.6 Brittle Fracture of Ceramics 9.7 Fracture of Polymers 9.8 Fracture Toughness Testing 9.9 Cyclic Stresses 9.10 The S-N Curve 9.11 Fatigue in Polymeric Materials 9.12 Crack Initiation and Propagation 9.13 Factors That Affect Fatigue Life 9.14 Environmental Effects 9.15 Generalized Creep Behavior 9.16 Stress and Temperature Effects 9.17 Data Extrapolation Methods 9.18 Alloys for High-Temperature Use 9.19 Creep in Ceramic and Polymeric Materials Chapter 10 - Phase Diagrams 10.1 Introduction 10.2 Solubility Limit 10.3 Phases 10.4 Microstructure 10.5 Phase Equilibria 10.6 One-Component (or Unary) Phase Diagrams 10.7 Binary Isomorphous Systems 10.8 Interpretation of Phase Diagrams 10.9 Development of Microstructure in Isomorphous Alloys 10.10 Mechanical Properties of Isomorphous Alloys 10.11 Binary Eutectic Systems Materials of Importance-Lead-Free Solders 10.12 Development of Microstructure in Eutectic Alloys 10.13 Equilibrium Diagrams Having Intermediate Phases or Compounds 10.14 Eutectoid and Peritectic Reactions 10.15 Congruent Phase Transformations 10.16 Ceramic Phase Diagrams 10.17 Ternary Phase Diagrams 10.18 The Gibbs Phase Rule 10.19 The Iron-Iron Carbide (Fe-Fe3C) Phase Diagram 10.20 Development of Microstructure in Iron-Carbon Alloys 10.21 The Influence of Other Alloying Elements Chapter 11 - Phase Transformations 11.1 Introduction 11.2 Basic Concepts 11.3 The Kinetics of Phase Transformations 11.4 Metastable versus Equilibrium States 11.5 Isothermal Transformation Diagrams 11.6 Continuous-Cooling Transformation Diagrams 11.7 Mechanical Behavior of Iron-Carbon Alloys 11.8 Tempered Martensite 11.9 Review of Phase Transformations and Mechanical Properties for Iron-Carbon Alloys Materials of Importance-Shape-Memory Alloys 11.10 Heat Treatments 11.11 Mechanism of Hardening 11.12 Miscellaneous Considerations 11.13 Crystallization 11.14 Melting 11.15 The Glass Transition 11.16 Melting and Glass Transition Temperatures 11.17 Factors That Influence Melting and Glass Transition Temperatures Chapter 12 - Electrical Properties 12.1 Introduction 12.2 Ohm's Law 12.3 Electrical Conductivity 12.4 Electronic and Ionic Conduction 12.5 Energy Band Structures in Solids 12.6 Conduction in Terms of Band and Atomic Bonding Models 12.7 Electron Mobility 12.8 Electrical Resistivity of Metals 12.9 Electrical Characteristics of Commercial Alloys Materials of Importance-Aluminum Electrical Wires 12.10 Intrinsic Semiconduction 12.11 Extrinsic Semiconduction 12.12 The Temperature Dependence of Carrier Concentration 12.13 Factors that Affect Carrier Mobility 12.14 The Hall Effect 12.15 Semiconductor Devices 12.16 Conduction in Ionic Materials 12.17 Electrical Properties of Polymer 12.18 Capacitance 12.19 Field Vectors and Polarization 12.20 Types of Polarization 12.21 Frequency Dependence of the Dielectric Constant 12.22 Dielectric Strength 12.23 Dielectric Materials 12.24 Ferroelectricity 12.25 Piezoelectricity Chapter 13 - Types and Applications of Materials 13.1 Introduction 13.2 Ferrous Alloys 13.3 Nonferrous Alloys Materials of Importance-Metal Alloys Used for Euro Coins 13.4 Glasses 13.5 Glass-Ceramics.
Includes index.
PB
Keywords: Materials; TECHNOLOGY & ENGINEERING / Material Science